PENERAPAN MODEL CTL (CONTEXTUAL TEACHING AND LEARNING) BERBANTUAN GAME INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN - Pribadi, Wicaksono; Liyana, Nurul; Handayani, Agit; Sudarmiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model assisted by interactive games in improving the ability of children aged 5–6 years to sort organic and inorganic waste. The study is motivated by the importance of fostering environmental awareness from an early age and the limited effectiveness of conventional learning methods that tend to be monotonous and less contextual. The research employed a Classroom Action Research (CAR) design conducted at TK Negeri Pembina, Madiun City, involving children in Group B aged 5–6 years. Data were collected through observation using assessment rubrics focusing on children’s independence and responsibility. The results indicate that the CTL model assisted by interactive games effectively improves children’s ability to identify, differentiate, and properly sort organic and inorganic waste. In addition, this learning approach positively influences the development of independence and responsibility, which generally reached the category of Developing as Expected. These findings suggest that contextual learning integrated with interactive technology provides meaningful, engaging, and developmentally appropriate learning experiences for early childhood learners.